I Feel ‘Being Outcast’: A Case of Hura brasiliensis - Goel, Aman (Homœopathic Links, 2017)
This is a case based on my personal experience at Cure Foundation, Meerut, with the remedy Hura brasiliensis. In accordance with the sensation way of practicing homeopathy, this case study reveals the essence of Hura brasiliensis, as a remedy while understanding the core value of Leprosy miasm in the autoimmune disease of psoriasis. Hura brasiliensis, being the principle remedy of Leprosy miasm, incorporates the sensation of ‘being outcast’ from the world and ‘being unfortunate’.
Keywords: Psoriasis; Hura brasiliensis; Leprosy miasm; Outcast; Unfortunate; Psoriasis Life Stress Inventory Scale